Keterlibatan Kader Kesehatan dalam Merespon Pandemi COVID-19 : Sebuah Studi Fenomenologi - Syamikar Baridwan Syamsir; Agus Setiawan; Henny Permatasari; Bani Bacan Hacantya Yudanagara; Heru Supriyatno (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Since the establishment of COVID-19 as a global pandemic, at the same time it has had an impact on many aspects including the health system. Various efforts have been made both at the global and national levels. Active participation from the community through the involvement of health cadres has an important role in handling a pandemic. This study aims to explore the involvement of health cadres as part of community members in responding to the COVID-19 pandemic, especially in the community. This study used a descriptive phenomenological study with semi-structured in-depth interviews involving 13 health cadres in Makassar City who were selected using a purposive sampling technique. Data were analyzed using thematic analysis with the Colaizzi data analysis method. The results of this study indicate that various roles have been carried out by health cadres during the COVID-19 pandemic. There are at least three (3) main themes generated in this study, namely, (1) providing education and health promotion for COVID-19; (2) implementing community-based surveillance (SBM) as a strategy for handling the COVID-19 pandemic; (3) helping maintain essential health services during the COVID-19 pandemic. The emergence of COVID-19 as a global pandemic has brought major changes to the order of people's lives in various aspects, including aspects of the health care system. Handling this pandemic is of course not only the responsibility of the government but also the shared responsibility of all levels of society. Health cadres as part of the community members have a vital role to help accelerate the handling and control of the pandemic.